Persistent fever with chills and an endocardial mass in a child: an unusual presentation of Hughes–Stovin syndrome. (11th November 2016) - Fabi, Marianna; Lami, Francesca; Zompatori, Maurizio
Abstract: A 12-year-old boy with a right atrium endocardial mass was initially diagnosed as having Lemierre's syndrome on the basis of previous mastoiditis and jugular vein and cerebral venous thrombosis. Lack of response to antibiotics, persistent high fever with chills, acute-phase reactants, and peripheral arterial pseudoaneurysms made us reconsider the diagnosis. Only after the late appearance of radiological pulmonary lesions and recognition of pulmonary artery aneurysms, Hughes–Stovin syndrome was diagnosed. Hughes–Stovin syndrome is an exceedingly rare vasculitis, especially in childhood, consisting of multiple pulmonary artery aneurysms and deep venous thromboses. The lack of formal diagnostic criteria and the rarity of the disease make the diagnosis very challenging, especially when respiratory complaints are not present at onset, as in the presented case. The treatment aims to reduce inflammation, although there is debate about anticoagulation therapy because of the risk of pulmonary haemorrhage.